2008
DOI: 10.1021/ol8017038
|View full text |Cite
|
Sign up to set email alerts
|

Is Donor−Acceptor Hydrogen Bonding Necessary for 4,6-O-Benzylidene-directed β-Mannopyranosylation? Stereoselective Synthesis of β-C-Mannopyranosides and α-C-Glucopyranosides

Abstract: 2,3-Di-O-benzyl-4,6-O-benzylidene-thiohexopyranosides, on activation with 1-benzenesulfinyl piperidine and triflic anhydride, react with allyl silanes and stannanes, and with silyl enolethers to give C-glycosides. In mannose the β-isomers are formed selectively whereas the glucose series provides the α-anomers. This selectivity pattern parallels that of O-glycoside formation and eliminates the need to consider donor-acceptor hydrogen bonding in the formation of the O-glycosides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 31 publications
6
41
0
Order By: Relevance
“…This is because simple 4,6- O -benzylidene protected α- C -glucopyranosides, with an axial substituent at C1 but lacking the third ring, exist predominantly as 4 C 1 conformers (vide infra). 8081 …”
Section: Resultsmentioning
confidence: 99%
“…This is because simple 4,6- O -benzylidene protected α- C -glucopyranosides, with an axial substituent at C1 but lacking the third ring, exist predominantly as 4 C 1 conformers (vide infra). 8081 …”
Section: Resultsmentioning
confidence: 99%
“…[13] Crich and Sharma have demonstrated that hydrogen bonding between glycosyl donors and acceptors is not an important factor in determining the stereoselectivity of glycosylation reactions. [36] Geometries were optimised using B3LYP/6-31G* [37] in Gaussian 03. [38] Additional single-point calculations using M06/6-31 + G** [39] were performed in Gaussian 09 [40] and gave results that correlated well with the original B3LYP/6-31G* calculations (see the Supporting Information).…”
Section: Wwwchemeurjorgmentioning
confidence: 99%
“…Along with the previously described allylsilane additions, Crich and Sharma also reported the reaction of several different silyl enol ethers with thiomannoside 10 (Scheme 28) [134]. The b-C-mannosides were obtained with good overall selectivity and yield.…”
Section: [ ( S C H E M E _ 2 1 ) T D $ F I G ]mentioning
confidence: 89%
“…The authors noted that this selectivity was highly dependent on the presence of the benzylidene acetal and was also the result of tight ion pairs in the transition state, as in the case of the corresponding O-b-mannosides (Scheme 20) [134].…”
Section: [ ( S C H E M E _ 2 1 ) T D $ F I G ]mentioning
confidence: 99%